Oxytocin-Gaze Positive Loop and the Coevolution of Human-Dog Bonds. Issue 7 (July 2015) - Nagasawa, Miho; Mitsui, Shouhei; En, Shiori; Ohtani, Nobuyo; Ohta, Mitsuaki; Sakuma, Yasuo; Onaka, Tatsushi; Mogi, Kazutaka; Kikusui, Takefumi
Abstract : ABSTRACT: Mutual gaze is the most fundamental manifestation of social bonding in humans between mothers and infants and between sexual partners in monogamous species. Dog-to-owner gaze probably evolved as a form of social communication during domestication with humans, leading to the establishment of a human-dog bond that is similar to a mother-infant relationship. Urinary oxytocin increases in mothers following mutual gaze in both mothers and infants. A rise in urinary oxytocin occurs in dogs following mutual gaze, but it is unclear whether the increase also occurs in dog owners. This study investigated the effect of mutual gaze in both dogs and their owners on levels of urinary oxytocin. A primary aim was to determine whether there is a causal relationship between mutual gaze and the release of oxytocin. The authors tested the hypothesis that an oxytocin-mediated positive loop (as has been postulated between mother and infants) exists between humans and dogs that is mediated by gaze. To show that the hormone was a cause not just an effect of the interaction, oxytocin was administered intranasally to dogs, and the gazing interaction between dogs and their owners as well as unfamiliar humans was assessed. Gazing behavior increased urinary oxytocin in dogs as well as their owners. Owners and dogs sharing a long mutual gaze had higher levels of oxytocin in their urine than did owners and dogs with shorter eye contact. Although a prolonged gaze increased oxytocin in dogs, it did not increase levels of oxytoxin in hand-raised pet wolves, suggesting that mutual gaze is not used in wolves as a form of social communication with humans. Female dogs receiving intranasal oxytocin gazed longer at their owners than did those given saline. Moreover, oxytocin levels were increased by intranasal oxytocin in dog owners (who had not been given this hormone). These mutual effects were not seen between dogs and unfamiliar humans or between male dogs and their owners. These findings indicate that oxytocin is the cause, not the effect, of the interaction and support of the existence of an interspecies self-perpetuating oxytocin-mediated positive loop facilitated and modulated by mutual gazing. Gazing behavior may have supported the coevolution of human-dog bonding as a common mode of communicating social attachment.